Raman spectroscopic investigation of the effects of cosmetic formulations on the constituents and properties of human skin - Gaspar Tosato, Maira (2012)
Objective: This study aimed to investigate the biochemical alterations in hydration and skin proteins, which are associated with the skin aging process, caused by cosmetic use. Background data: Many techniques have been used to assess the effectiveness of cosmetics' hydrating and anti-aging effects on skin. Recently, Raman spectroscopy has been shown to be a powerful, noninvasive tool that can monitor changes in the biomolecules of the skin in real time. Materials and methods: Were analyzed human skin in vivo at the beginning of the experiment (T0) and after 30 (T30) and 60 (T60) days of continuous use of a cosmetic product. Fourier-transform and dispersive Raman spectroscopy were the used to examine the periorbicular right lateral eye region of 16 female Brazilian volunteers, aged 60-75 years. Multivariate statistical analysis of principal components analysis (PCA) and linear discriminant analysis were performed on all Raman spectra. Results: Using the cosmetic product for 30 days increased the intensity of the Raman bands for collagen, amide III (1250-1350cm-1) for proteins, and the water (OH) stretching mode at 3250cm-1, suggesting that the treatment was effective. The changes observed at T30 were not sustained at the same intensity for 60 days. Intensity variations in other bands may be related to changes in the organization of the epidermis at the dermal matrix. Conclusions: The application of cosmetics with active moisturizing and anti-aging properties helps to maintain the skin's protective barrier and to slow the intrinsic and extrinsic aging processes of the skin. © 2012, Mary Ann Liebert, Inc.